Respuesta :
x^2-2x-24 = (x - 6)(x + 4)
cause
(x - 6)(x + 4)
= x^2 - 6x + 4x - 24
= x^2 - 2x - 24
answer
(x - 6)(x + 4)
hope it helps
cause
(x - 6)(x + 4)
= x^2 - 6x + 4x - 24
= x^2 - 2x - 24
answer
(x - 6)(x + 4)
hope it helps
Answer:
(x+4)(x−6)
Step-by-step explanation:
Factoring x2−2x−24
x2−2x−24
The middle number is -2 and the last number is -24.
Factoring means we want something like
(x+_)(x+_)
Which numbers go in the blanks?
We need two numbers that...
Add together to get -2
Multiply together to get -24
Can you think of the two numbers?
Try 4 and -6:
4+-6 = -2
4*-6 = -24
Fill in the blanks in
(x+_)(x+_)
with 4 and -6 to get...
(x+4)(x-6)